Pemberdayaan Masyarakat Dengan Pemanfaatan Daun Bakung (Crynum Asiaticum L) Dalam Meredakan Rematik Pada Persendian Lansia Di Desa Ujung Gurap - Nasution, Nurul Hidayah; Ritonga, Sukhri Herianto; Nurlaila, Nurlaila; Dalimunthe, Abdul Rahim; Harahap, Nova Khairani; Simamora, Della Yusra; Jufri, Soleman (Universitas Aufa Royhan Di Kota Padangsidipuan, 2023)
Modern society does not have much time and adequate rest. The high demands of work and limited time make them trapped in stress. As a result, many people experience various health problems. One of these diseases is rheumatism. Rheumatism or rheumatoid arthritis is a condition that can cause pain, swelling and a burning sensation in the joints. This activity has the benefit of increasing community knowledge and skills in the hope of creating community independence so that the elderly can be healthy, independent, active and productive. This activity uses a participatory model that involves community components such as village heads, elderly cadres and the community, especially the elderly. The number of participants was 30 people. The location of this community service was carried out in the Ujung Gurap Village Hall, Padangsidimpuan Batunadua District, Padangsidimpuan City. This type of service is health promotion by providing information, demonstrating the use and use of lily leaves. The methods used in this activity include providing information, demonstrations, training, discussions and questions and answers. The media used in this activity are leaflets, guidebooks and ppt slides. The final result that can be seen from this training activity is that the majority of people are able to know the materials and tools needed to practice using daffodil leaves and know exactly the steps needed in the process of using them. The community looked orderly and in accordance with what was directed by the team in this activity. The activity of practicing the use of lily leaves to relieve rheumatic pain in the elderly in Ujung Gurap Village was successfully carried out.